2010
DOI: 10.1002/ca.21061
|View full text |Cite
|
Sign up to set email alerts
|

Variable morphology of the suprascapular notch: An investigation and quantitative measurements in Chinese population

Abstract: Although several morphological variations and classification of the suprascapular notch (SSN) were reported in western populations, little attention has been paid to this anatomic issue in the Chinese population. In this research of SSN morphology in Chinese people, 295 specimens of intact dry Chinese adult scapulas were investigated and measured thoroughly and systematically. Morphological features of SSN variations were observed by visual inspection, and correlation parameters of variability and classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 19 publications
6
52
5
Order By: Relevance
“…This corresponds with the results of Wang et al (Chinese population) where also the most common type of SSN reported is Type II (58.6%) , where the notch is longest in transverse diameter and the least common is Type V where both notch and foramen are present (none). 8 Natsis et al in their study reported an equal incidence of types II and III SSN. 5 On gross examination without involving any measurements, the results of the present study correspond with that of Sinkeet et al who also reported the U shaped notch as most common (29%) and the complete ossification of STSL as least common (4%) in Kenyan population.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This corresponds with the results of Wang et al (Chinese population) where also the most common type of SSN reported is Type II (58.6%) , where the notch is longest in transverse diameter and the least common is Type V where both notch and foramen are present (none). 8 Natsis et al in their study reported an equal incidence of types II and III SSN. 5 On gross examination without involving any measurements, the results of the present study correspond with that of Sinkeet et al who also reported the U shaped notch as most common (29%) and the complete ossification of STSL as least common (4%) in Kenyan population.…”
Section: Discussionmentioning
confidence: 85%
“…3 SSN has been classified by various workers in different populations on the basis of parameters such as vertical length of the notch, transverse diameter of the notch and shape of the notch. 4,5,6,7,8 Knowing the anatomical variations in detail is better for understanding of location and source of the entrapment syndrome.However, the literature focusing on SSN and SN IJBAR (2013) 04 (01) www.ssjournals.com…”
Section: Introductionmentioning
confidence: 99%
“…Therefore various studies have been done on suprascapular notch variations in different populations. Rengachary et al, [6] Ticker et al, [11], Bayramoglu et al, [12] Natsis et al, [13] Sinkeet [14] Wang [15] and Polguj [16]. Depending on the shape of suprascapular notch and the degree of ossification, Rengachary et al, [6] classified SSN into six types .…”
Section: Resultsmentioning
confidence: 99%
“…Iqbal et al [13] separated the notches into 3 types -"U", "V" and "J" types, without involving any measurements. Wang et al [37] have found a new variable morphology of the SSN with a double suprascapular foramen. The classification of SSN that was used in our study is simple and does not require complicated measurements, and it makes possible to very easily distinguish the three types of the notch -its absence (type 1) and the partial and complete ossification of the superior transverse suprascapular ligament (types 4 and 5), which are supposed to be risk factors for suprascapular entrapment neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wang et al [37] and Soni et al [33], the most common type in their samples is the type, where the notch has longer transversal diameter than the vertical length. The results of Natsis et al [19] show an equal inci- dence of the types, where the notch is longest in its transverse diameter or it is longest in its vertical length.…”
Section: Discussionmentioning
confidence: 99%